Market volatility and models for forecasting volatility - Bulut, Emre (IGI Global, 2024)
This chapter delves into market volatility and its forecasting models in the dynamic financial landscape. It examines factors driving volatility, quantification approaches, and diverse models. From traditional to advanced models and deep learning techniques like RNNs, LSTMs, BiLSTMs, and GRUs, it enriches our understanding of market dynamics. These models are vital for risk management, strategic investment, and informed decisions, offering insights into volatile asset price fluctuations. By embracing data-driven solutions and predictive analytics, the authors navigate market unpredictability, led by models serving as custodians of comprehension and stability, guiding towards enlightened, strategic, and prosperous financial decisions. © 2024 by IGI Global. All rights reserved.